Efficacy of the ECHOMANTRA online intervention to support recovery from anorexia nervosa in adult patients: study protocol of a randomized controlled multi-center trial - Yolanda Quiles; Álvaro Ruiz; Eva León-Zarceño; Javier Manchón; Marie-Carmen Neipp; Sofía Payá-López; Katina Kovacheva; Valentina Cardi (Journal of Eating Disorders)
Abstract Background Poor quality of life in adults with anorexia nervosa (AN) and persistent high rates of readmission highlight the necessity of developing interventions to optimize treatment outcomes. ECHOMANTRA is a novel online intervention based on interventions for carers (Experienced Carers Helping Others, ECHO) and patients (Maudsley Model of Anorexia Nervosa Treatment for Adults, MANTRA) with anorexia nervosa. The objective of this paper is to describe the study protocol of a randomized control trial (RCT) aimed at evaluating the efficacy of an adaptation of the ECHOMANTRA for adults AN inpatients and outpatients, and their carers, to be implemented as an add-on to treatment-as-usual (TAU). Methods In a multi − center pilot randomized controlled trial (RCT), 148 adult AN patients, and their carers, will be randomized to receive treatment as usual (TAU) or TAU plus ECHOMANTRA. Assessments will take place at baseline (T0), post-intervention (2-month) (T1), 6-month follow-up (T2), and 12-month follow-up (T3). Primary outcomes will be eating disorder psychopathology and psychological well-being. For carers, outcome variables will include psychological well-being, accommodation and enabling behaviors, expressed emotion, illness burden, quality of life and care skills. Discussion This study will provide evidence of the efficacy of this novel, online and protocolized intervention in facilitating the recovery of these patients. Trial registration ISRCTN registry (Identifier: 80253157 https://doi.org/10.1186/ISRCTN80253157 ).